2017
DOI: 10.1111/jdv.14195
|View full text |Cite
|
Sign up to set email alerts
|

A European subset analysis from the population‐based Multinational Assessment of Psoriasis and Psoriatic Arthritis shows country‐specific features: results from psoriasis patients in Spain

Abstract: BackgroundThe Multinational Assessment of Psoriasis and Psoriatic Arthritis (MAPP) survey data were not analysed to account for cultural and healthcare system differences across European countries (EC).ObjectiveTo utilize MAPP data to characterize psoriasis in Spanish patients, including severity assessment and Dermatology Life Quality Index (DLQI).MethodsThe MAPP survey was conducted between June and August 2012. This analysis included 1700 patients with self‐reported psoriasis (without psoriatic arthritis) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…IL-17 inhibitors were also found to be effective in the management of patients with the palmoplantar phenotype, which is found in 20% to 40% of psoriasis patients. 43-46 GESTURE was a PPP-specific, double-blind phase IIIb trial that randomized 205 patients with moderate to severe PPP (≥ 3 on the 5-point Palmoplantar Investigator Global Assessment [ppIGA] scale) and at least 1 additional plaque not on the palms or soles to confirm plaque psoriasis (ie, low nonpalmoplantar involvement) to secukinumab (300 mg or 150 mg) or placebo. 47 At 16 weeks, secukinumab was associated with significant achievement of clear or almost clear palms and soles on the (ppIGA 0-1) vs placebo (Table 5).…”
Section: Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…IL-17 inhibitors were also found to be effective in the management of patients with the palmoplantar phenotype, which is found in 20% to 40% of psoriasis patients. 43-46 GESTURE was a PPP-specific, double-blind phase IIIb trial that randomized 205 patients with moderate to severe PPP (≥ 3 on the 5-point Palmoplantar Investigator Global Assessment [ppIGA] scale) and at least 1 additional plaque not on the palms or soles to confirm plaque psoriasis (ie, low nonpalmoplantar involvement) to secukinumab (300 mg or 150 mg) or placebo. 47 At 16 weeks, secukinumab was associated with significant achievement of clear or almost clear palms and soles on the (ppIGA 0-1) vs placebo (Table 5).…”
Section: Psoriasismentioning
confidence: 99%
“…Scalp involvement develops in 40% to 90% of psoriasis patients, and the scalp is the first site to be affected in up to one-half of cases. 44,58-61 Evaluations of QoL in patients with scalp psoriasis indicate that it is associated with a disproportionately negative impact relative to the BSA affected. More than one-half of patients indicated that their condition was socially and psychologically distressing, and itching and scaling were identified as the most common and most troubling symptoms.…”
Section: Psoriasismentioning
confidence: 99%
“…Six of these 10 patients (60%) were resistant to at least one previous biological agent and three of them (30%) were resistant to more than one biological agent. However, in real‐world practice, most patients on secukinumab have previously received biologics . Our series might more accurately represent the population receiving secukinumab in the clinic.…”
Section: Summary Of the 10 Cases Of Erythrodermic Psoriasismentioning
confidence: 99%
“…However, in real-world practice, most patients on secukinumab have previously received biologics. 7 Our series might more accurately represent the population receiving secukinumab in the clinic. It suggests that the real treatment effects of biologics may be compromised in comparison with the original studies.…”
mentioning
confidence: 99%
“…Medical therapy for psoriasis has classically included topical and systemic treatments such as phototherapy, retinoids, methotrexate, and cyclosporine [3]. In the last few years, biologic treatment has become the established therapeutic standard for significant improvement of the quality of life of patients with moderate to severe psoriasis [4]. The involvement of oxidative stress in the pathogenesis of psoriasis has been recently proposed.…”
Section: Introductionmentioning
confidence: 99%